Crop rotation complexity affects soil properties shaping antibiotic resistance gene types and resistance mechanisms - Hu, Rong; Liu, Yang; Wen, Mengmeng; Zhou, Nafang; Wang, Jun (Frontiers in Microbiology, 2025)
Crop rotation enhances agricultural productivity and soil fertility but may also contribute to the accumulation of antibiotic resistance genes (ARGs). However, the changes in soil ARGs and their associated resistance mechanisms under different crop rotation regimes are not well understood. In this study, we employed metagenomics to comprehensively investigate soil ARGs under different crop rotation regimes and complexity. Our findings revealed that soil properties varied significantly with crop rotation regime and complexity. Specifically, soil pH and the total carbon/nitrogen ratio (C/N) were the highest in bare land (BL) and gradually decreased in the order non-rotation, simple rotation, and complex rotation systems. The composition of soil ARGs exhibited significant differentiation by crop rotation complexity. Furthermore, differential gene analysis identified four specific types of ARGs—glycopeptide, multidrug, fluoroquinolone, and macrolide-lincosamide-streptogramin B (MLSB)—and two resistance mechanisms—cellular protection and efflux pump. Notably, soil microbial biomass carbon, soil microbial biomass nitrogen, and soil organic carbon are significantly correlated with ARGs in complex crop rotation systems, whereas soil pH and C/N ratio show significant associations in BL. The C/N ratio was identified as the most relevant determinant for glycopeptide, multidrug, fluoroquinolone, and MLSB resistance genes. Overall, these findings elucidate key factors associated with ARGs under long-term crop rotation, thereby providing valuable insights into the influence of crop rotation regimes on soil ARGs and enhancing soil fertility by improving soil properties.